IDentif.AI: Rapidly optimizing combination therapy design against severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov-2) with digital drug development - Blasiak, Agata (Wiley, 2023)
Bioengineering & Translational Medicine